Gel-state polymer electrolyte as well as preparation method and application thereof
By using in situ polymerization of specific components in gel polymer electrolytes to form a three-dimensional network, the problems of low lithium ion migration number and ionic conductivity are solved, and efficient lithium ion transport and battery performance improvement are achieved.
Patent Information
- Application Number
- CN202510957521.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-10-17
AI Technical Summary
The existing gel polymer electrolytes have low lithium ion migration numbers and ionic conductivity in all-solid-state batteries, resulting in slow lithium ion migration rate, increased concentration polarization and battery polarization, and ionic conductivity unable to reach the industrialization threshold.
A combination of polar organic solvents, lithium salts, lithium salt additives, liquid flame retardants, liquid monomers and initiators is used to form a three-dimensional polymer network through in-situ polymerization, optimize the ion transport pathway, weaken the solvation structure of the lithium salt, and increase the lithium ion migration number and ionic conductivity.
It significantly improves the lithium ion migration number and ion conductivity, enhances the battery's cycle performance and capacity retention rate, and meets industrialization needs.
Smart Images

Figure CN120809951A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of batteries, in particular to a gel-state polymer electrolyte and a preparation method and application thereof. BACKGROUND
[0002] Lithium ion batteries, as an important part of modern energy storage, provide efficient energy for many fields. In recent years, all-solid-state batteries are considered as an effective way to improve energy density and safety. However, in the field of all-solid-state batteries, the gel-state polymer (GPE) electrolyte used is limited by Li + The strong solvation effect between solvent molecules, the lithium ion transference number (usually <0.5) is significantly lower than that of liquid electrolyte, which leads to Li + Slow migration rate, which exacerbates concentration polarization and battery polarization; in addition, the room temperature ionic conductivity of the existing GPE electrolyte is generally lower than the industrialization threshold (2 mS cm -1 )。 SUMMARY
[0003] The present application provides a gel-state polymer electrolyte and a preparation method and application thereof, the gel-state polymer electrolyte of the present application has high lithium ion transference number and ionic conductivity.
[0004] The present application provides a gel-state polymer electrolyte comprising the following raw materials for preparation:
[0005] Polar organic solvent, lithium salt, lithium salt additive, liquid flame retardant, liquid monomer and initiator;
[0006] The polar organic solvent comprises 1,3-dioxolane and ethylene glycol dimethyl ether;
[0007] The use amount ratio of the lithium salt to the polar organic solvent is 1 mmol: 0.5-2 mL;
[0008] The mass of the lithium salt additive is 1.5-5% of the total mass of the lithium salt and the polar organic solvent;
[0009] The volume of the liquid flame retardant is 10-20% of the volume of the polar organic solvent;
[0010] The volume of the liquid monomer is 10-20% of the volume of the polar organic solvent;
[0011] The mass of the initiator is 0.5-2% of the total mass of the lithium salt, the polar organic solvent and the liquid monomer.
[0012] Preferably, the volume ratio of the 1,3-dioxolane and the ethylene glycol dimethyl ether is 1:0.5-2.
[0013] Preferably, the lithium salt comprises one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bisoxalate borate, lithium bistrifluoromethanesulfonylimide, and lithium bisfluorosulfonylimide.
[0014] Preferably, the lithium salt additive comprises one or more of derivatized asymmetric (fluorosulfonyl) (trifluoromethylsulfonyl) imide lithium, lithium hexafluorophosphate, lithium difluorodioxalate phosphate, lithium difluorophosphate, lithium tetrafluorooxalate phosphate, lithium difluorooxalate borate, and lithium nitrate.
[0015] Preferably, the liquid flame retardant comprises an organophosphorus flame retardant, a nitrogen-containing flame retardant, and a fluorine-containing flame retardant.
[0016] The organophosphorus flame retardant comprises one or more of trimethyl phosphate, triethyl phosphate, triphenyl phosphate, diethyl (2,2,2-trifluoroethyl) phosphate, and triethyl hexafluorophosphate.
[0017] The nitrogen-containing flame retardant comprises melamine cyanurate and / or melamine.
[0018] The fluorine-containing flame retardant comprises one or more of bis (2,2,2-trifluoroethyl) phosphate, perfluoropolyether, ethoxy (pentafluoro) cyclotriphosphazene, and 1-ethyl-3-methylimidazolium hexafluorophosphate.
[0019] Preferably, the liquid monomer comprises one or more of a polyether monomer, an acrylate monomer, and a fluorine-containing monomer.
[0020] The polyether monomer comprises ethylene oxide and / or propylene oxide.
[0021] The acrylate monomer comprises polymethyl methacrylate and / or polyethylene glycol diacrylate.
[0022] The fluorine-containing monomer comprises vinylidene fluoride and / or Nafion precursor.
[0023] Preferably, the initiator comprises a peroxide thermal initiator and / or an azo thermal initiator.
[0024] The peroxide thermal initiator comprises dibenzoyl peroxide and / or dicumyl peroxide.
[0025] The azo thermal initiator comprises azobisisobutyronitrile and / or diethyl azodicarboxylate.
[0026] The present application also provides a preparation method of the gel-state polymer electrolyte described in the above technical solution, comprising the following steps:
[0027] After the raw materials of the gel-state polymer electrolyte are mixed, in-situ polymerization is performed to obtain the gel-state polymer electrolyte.
[0028] Preferably, the temperature of the in-situ polymerization is 50-70℃, and the time is 4-12h.
[0029] The application also provides the application of the gel polymer electrolyte prepared by the preparation method in a lithium ion battery.
[0030] The application adjusts the type of solvent to form a solvation structure, which can weaken the coordination of Li + in the lithium salt and release it, thereby improving the lithium ion migration number and ionic conductivity.
[0031] The application uses an in-situ polymerization strategy to construct a three-dimensional polymer network. The network not only provides rich polar sites (such as ether oxygen groups) to promote lithium ion hopping, but also optimizes the ion transmission path, further improving the ionic conductivity. BRIEF DESCRIPTION OF DRAWINGS
[0032] Figure 1 The flowchart for preparing the gel polymer electrolyte of the embodiment of the application is shown in the figure;
[0033] Figure 2 The cycle performance graph of the battery assembled by the GPE electrolyte of Example 1 is shown in the figure;
[0034] Figure 3 The electrochemical performance data of the GPE electrolyte obtained in Example 1 is shown in the figure;
[0035] Figure 4 The electrochemical performance data of the GPE electrolyte obtained in Comparative Example 1 is shown in the figure;
[0036] Figure 5 The electrochemical performance data of the GPE electrolyte obtained in Comparative Example 2 is shown in the figure;
[0037] Figure 6 The electrochemical performance data of the GPE electrolyte obtained in Comparative Example 3 is shown in the figure. DETAILED DESCRIPTION
[0038] The application provides a gel polymer electrolyte, which comprises the following preparation raw materials:
[0039] a polar organic solvent, a lithium salt, a lithium salt additive, a liquid flame retardant, a liquid monomer, and an initiator;
[0040] The polar organic solvent comprises 1,3-dioxolane and ethylene glycol dimethyl ether.
[0041] The use amount ratio of the lithium salt to the polar organic solvent is 1mmol: 0.5-2mL.
[0042] The mass of the lithium salt additive is 1.5-5% of the total mass of the lithium salt and the polar organic solvent;
[0043] The volume of the liquid monomer is 10-20% of the volume of the polar organic solvent;
[0044] The volume of the liquid monomer is 10-20% of the volume of the polar organic solvent;
[0045] The mass of the initiator is 0.5-2% of the total mass of the lithium salt, the polar organic solvent and the monomer.
[0046] In the present application, the preparation raw material of the gel polymer electrolyte comprises a polar organic solvent, which comprises 1,3-dioxolane (DOL) and dimethoxyethane (DME); the volume ratio of the 1,3-dioxolane and dimethoxyethane is preferably 1:0.5-2, and in specific embodiments of the present application, the volume ratio of the 1,3-dioxolane and dimethoxyethane can be 1:1.
[0047] In the present application, the preparation raw material of the gel polymer electrolyte comprises a lithium salt, and the use amount ratio of the lithium salt to the polar organic solvent is 1 mmol:0.5-2 mL, and in specific embodiments of the present application, the use amount ratio of the lithium salt to the polar organic solvent can be 1 mmol:1 mL or 1 mmol:1.5 mL; the lithium salt preferably comprises one or more of lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium bis(fluorosulfonyl)imide (LiFSI).
[0048] In the present application, the preparation raw material of the gel polymer electrolyte comprises a lithium salt additive, and the mass of the lithium salt additive is 1.5-5% of the total mass of the lithium salt and the polar organic solvent, and in specific embodiments of the present application, the mass of the lithium salt additive is preferably 1.5%, 2.0%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5.0% of the mass of the lithium salt and the polar organic solvent; the lithium salt additive preferably comprises one or more of derivatized asymmetric (fluorosulfonyl)(trifluoromethanesulfonyl)imide lithium (LiFTFSI), lithium difluorophosphate (LiPF2O2), lithium difluorophosphate (LiPO2F2), lithium tetrafluorophosphate oxalate (LiFOP), lithium hexafluorophosphate (LiPF6), lithium difluoro borate oxalate (LiDFOB) and lithium nitrate (LiNO3).
[0049] In the present application, the preparation raw material of the gel-state polymer electrolyte comprises a liquid flame retardant, the volume of the liquid flame retardant is 10-20% of the volume of the polar organic solvent, in the specific embodiments of the present application, the volume of the liquid flame retardant can be 10%, 12%, 14%, 16%, 18% or 20% of the volume of the polar organic solvent; the liquid flame retardant preferably comprises an organic phosphorus-based flame retardant, a nitrogen-containing flame retardant and a fluorine-containing flame retardant; the organic phosphorus-based flame retardant preferably comprises one or more of trimethyl phosphate (TMP), triethyl phosphate (TEP), triphenyl phosphate (TPP), diethyl (2,2,2-trifluoroethyl) phosphate (DETFP) and triethyl hexafluorophosphate (HFTEP); the nitrogen-containing flame retardant preferably comprises melamine cyanurate and / or melamine;
[0050] The fluorine-containing flame retardant preferably comprises one or more of bis (2,2,2-trifluoroethyl) phosphate (BTFP), perfluoropolyether (PFPE), ethoxy (pentafluoro) cyclotriphosphazene (PFPN) and 1-ethyl-3-methyl imidazole hexafluorophosphate (EMIM-PF6), more preferably ethoxy (pentafluoro) cyclotriphosphazene. When the flame retardant is PFPN, the electrolyte is self-extinguished within 5s whether it is ignited by a lighter or a high-temperature spray gun.
[0051] In the present application, the preparation raw material of the gel-state polymer electrolyte comprises a liquid monomer, the volume of the liquid monomer is 10-20% of the volume of the polar organic solvent, in the specific embodiments of the present application, the volume of the liquid monomer is preferably 10%, 12%, 14%, 16%, 18% or 20% of the volume of the polar organic solvent, the liquid monomer preferably comprises one or more of a polyether-based monomer, an acrylate-based monomer and a fluorine-containing monomer; the polyether-based monomer preferably comprises oxirane and / or oxetane; the acrylate-based monomer preferably comprises polymethyl methacrylate and / or polyethylene glycol diacrylate; the fluorine-containing monomer preferably comprises vinylidene fluoride and / or Nafion precursor.
[0052] In the present application, the preparation raw material of the gel-state polymer electrolyte comprises an initiator, the mass of the initiator is preferably 0.5-2.0% of the total mass of the lithium salt, the polar organic solvent and the liquid monomer, in the specific embodiments of the present application, the mass of the initiator is preferably 0.5%, 1.0%, 1.5% or 2.0% of the total mass of the lithium salt, the polar organic solvent and the liquid monomer, the initiator preferably comprises a peroxide-based thermal initiator and / or an azo-based thermal initiator; the peroxide-based thermal initiator preferably comprises dibenzoyl peroxide and / or dicumyl peroxide; the azo-based thermal initiator preferably comprises azobisisobutyronitrile and / or diethyl azodicarboxylate.
[0053] The application further provides a preparation method of the gel-state polymer electrolyte.
[0054] The raw materials of the gel-state polymer electrolyte are mixed and then in-situ polymerized to obtain the gel-state polymer electrolyte.
[0055] In the application, the mixing is preferably performed in an argon glove box with O2<0.1 ppm and H2O<0.1 ppm.
[0056] In the application, the mixing preferably comprises:
[0057] The polar organic solvent, the lithium salt, the lithium salt additive and the liquid flame retardant are mixed and then mixed with the liquid monomer and the initiator.
[0058] In the application, the temperature of the in-situ polymerization is preferably 50-70 ℃, and the time is preferably 4-12 h. In the specific embodiments of the application, the temperature of the in-situ polymerization can be 55 ℃, 60 ℃ or 65 ℃, and the time can be 4 h, 6 h, 8 h, 10 h or 12 h.
[0059] The application further provides an application of the gel-state polymer electrolyte in a lithium ion battery.
[0060] The gel-state polymer electrolyte, the preparation method and the application thereof provided by the application are described in detail below in combination with examples, but they should not be understood as limiting the protection scope of the application.
[0061] Figure 1 A flow chart for preparing the gel-state polymer electrolyte in the embodiments of the application is as follows: two solvents are mixed, then the lithium salt and the additive are added to the mixed solvents, and then the monomer and the initiator are added, and then the obtained electrolyte is placed in an oven for thermal initiation polymerization.
[0062] The assembly process of the related batteries in the examples and comparative examples is as follows:
[0063] The assembly process of the Li||LFP full battery is as follows:
[0064] First, the LFP positive electrode sheet (with a diameter of 13 mm and a lithium iron phosphate loading of 10.0 mg cm -2), GPE electrolyte, polyethylene separator (diameter of 16 mm and thickness of 20 pm), and metal lithium negative electrode (diameter of 16 mm and thickness of 400 pm), and CR2025 button cell small buckle, CR 2025 button cell large buckle, steel sheet (diameter of 15.8 mm and thickness of 1.0 mm), and elastic sheet (diameter of 15.4 mm and thickness of 1.1 mm). Then, in an argon-filled glove box, the LFP positive electrode sheet was placed in the middle of the button cell small buckle, 25 pL of GPE electrolyte was dropped on the LFP positive electrode sheet by using a pipette gun to fully soak the positive electrode sheet, and the polyethylene separator was then stacked on the LFP positive electrode sheet, and 25 pL of GPE electrolyte was again dropped to fully soak the polyethylene separator. The metal lithium negative electrode, steel sheet, elastic sheet, and button cell large buckle were sequentially stacked on the polyethylene separator. After assembly, the battery was placed in a tablet press, and the battery was sealed and packaged at a pressure of 800 pa to ensure that the inside of the battery was not affected by external gas and water vapor.
[0065] The assembly process of the Li||NCM622 full battery is as follows:
[0066] First, the NCM622 positive electrode sheet (diameter of 13 mm and NCM622 loading of 4.0 mg cm -2 ), GPE electrolyte, polyethylene separator (diameter of 16 mm and thickness of 20 pm), and metal lithium negative electrode (diameter of 16 mm and thickness of 400 pm), and CR2025 button cell small buckle, CR 2025 button cell large buckle, steel sheet (diameter of 15.8 mm and thickness of 1.0 mm), and elastic sheet (diameter of 15.4 mm and thickness of 1.1 mm) were prepared. Then, in an argon-filled glove box, the NCM622 positive electrode sheet was placed in the middle of the button cell small buckle, 25 pL of GPE electrolyte was dropped on the NCM622 positive electrode sheet by using a pipette gun to fully soak the positive electrode sheet, and the polyethylene separator was then stacked on the NCM622 positive electrode sheet, and 25 pL of GPE electrolyte was again dropped to fully soak the polyethylene separator. The metal lithium negative electrode, steel sheet, elastic sheet, and button cell large buckle were sequentially stacked on the polyethylene separator. After assembly, the battery was placed in a tablet press, and the battery was sealed and packaged at a pressure of 800 pa to ensure that the inside of the battery was not affected by external gas and water vapor.
[0067] The assembly process of the pouch battery is as follows:
[0068] First, the LFP positive electrode sheet (size of 4 cm x 4 cm and lithium iron phosphate loading of 10.0 mg cm -2), GPE electrolyte, polyethylene separator (specification of 6 cm x 6 cm and thickness of 20 pm), lithium metal anode (specification of 5 cm x 5 cm and thickness of 50 pm) and aluminum plastic film (specification of 10 cm x 10 cm and thickness of 113 pm). Then, in the glove box filled with argon, the LFP positive electrode sheet was placed on the aluminum plastic film, 500 pL of GPE electrolyte was dropped on the LFP positive electrode sheet by using a pipette gun to fully soak the positive electrode sheet, the polyethylene separator was continued to be stacked on the LFP positive electrode sheet, 500 pL of GPE electrolyte was again dropped to fully soak the polyethylene separator, and the lithium metal and aluminum plastic film were continued to be stacked on the polyethylene separator in turn. After the assembly was completed, the pouch battery was heat-sealed to ensure that the inside of the battery was not affected by external gas and water vapor.
[0069] Example 1
[0070] 1 mL of DOL and 1 mL of DME were measured and mixed evenly, 0.574 g of LiTFSI, 0.374 g of LiFSI, 0.2 mL of PFPN and 0.05 g of LiNO3 were added to the mixed solvent, stirred for 5 min, and 0.4 mL of PEGDA monomer and 0.0296 g of AIBN initiator were continuously added, and after stirring evenly, it was placed in an oven for heat polymerization at 70°C for 4 h to prepare.
[0071] Figure 3 The electrochemical performance data of the GPE electrolyte obtained in Example 1 are as follows: Figure 3 Figure a is the conductivity data graph of the GPE electrolyte; Figure 3 Figure b is the chronopotentiometry test data graph of the GPE electrolyte.
[0072] From Figure 3 It can be seen that the conductivity of the GPE electrolyte obtained in Example 1 is 2.58 mS cm -1 The lithium ion transference number of the GPE electrolyte obtained in Example 1 is 0.92.
[0073] Figure 2 Figure is the cycle performance graph of the battery assembled by the GPE electrolyte of Example 1; Figure 2 Figure a is the cycle performance data graph of the Li||LFP full battery assembled; Figure 2 Figure b is the cycle performance data graph of the Li||NCM622 full battery assembled.
[0074] From Figure 2 It can be seen that in the full battery test, the high loading of 10 mg cm -2 The Li||LFP full battery assembled by the LFP cathode shows 143 mAh g -1The capacity retention rate of the Li||LFP full battery assembled using the LFP cathode after 85 cycles was 84%.
[0075] In addition, the capacity retention rate of the pouch battery assembled using 50 pm thin lithium and the LFP cathode after 85 cycles was 95%.
[0076] Example 2
[0077] 1 mL of DOL and 1 mL of DME were measured and mixed evenly, 0.574 g of LiTFSI, 0.374 g of LiFSI, 0.2 mL of PFPN, and 0.05 g of LiPF6 were added to the mixed solvent, stirred for 5 min, and 0.4 mL of PEGDA monomer and 0.0296 g of AIBN initiator were continuously added. After stirring evenly, it was placed in an oven for heat polymerization at 70°C for 4 h to prepare.
[0078] The conductivity of the GPE electrolyte obtained in Example 2 was 1.25 mS cm -1 , and the lithium ion transference number was 0.63.
[0079] In the full battery test, a high loading of 10 mg cm -2 The Li||LFP full battery assembled using the LFP cathode showed a capacity of 128 mAh g -1 after 300 cycles at a rate of 0.2C. The Li||NCM622 full battery assembled using a high-voltage NCM622 cathode with a cutoff voltage of 4.3V showed a capacity retention rate of 43% after 300 cycles at a rate of 0.2C. The capacity retention rate of the pouch battery assembled using 50 pm thin lithium and the LFP cathode after 85 cycles was 84%.
[0080] Example 3
[0081] 1 mL of DOL and 1 mL of DME were measured and mixed evenly, 0.574 g of LiTFSI, 0.374 g of LiFSI, 0.2 mL of PFPN, and 0.05 g of LiPF6 were added to the mixed solvent, stirred for 5 min, and 0.4 mL of PEGDA monomer and 0.0296 g of AIBN initiator were continuously added. After stirring evenly, it was placed in an oven for heat polymerization at 70°C for 4 h to prepare.
[0082] The conductivity of the GPE electrolyte obtained in Example 3 was 0.98 mS cm -1 , and the lithium ion transference number was 0.54.
[0083] In the full battery test, a high loading of 10 mg cm -2Li||LFP full cell assembled with LFP cathode shows 117 mAh g -1 of capacity after 300 cycles at 0.2C rate. Li||NCM622 full cell assembled with high voltage NCM622 cathode with cut-off voltage of 4.3V shows 39% capacity retention after 300 cycles at 0.2C rate. Pouch cell assembled with 50 pm thin lithium and LFP cathode shows 75% capacity retention after 85 cycles.
[0084] Example 4
[0085] Take 1 mL of DOL and 1 mL of DME, mix the two solvents evenly, add 0.574 g of LiTFSI, 0.374 g of LiFSI, 0.2 mL of TEPA and 0.05 g of LiPF6 to the mixed solvent, stir for 5 min, continue to add 0.4 mL of PMMA monomer and 0.0296 g of AIBN initiator, and stir evenly. After placing in an oven at 70°C for 4h, the prepared.
[0086] The conductivity of the GPE electrolyte obtained in Example 4 is 0.89 mS cm -1 , and the lithium ion transference number is 0.56.
[0087] In full cell testing, a high loading of 10 mg cm -2 Li||LFP full cell assembled with LFP cathode shows 108 mAh g -1 of capacity after 300 cycles at 0.2C rate. Li||NCM622 full cell assembled with high voltage NCM622 cathode with cut-off voltage of 4.3V shows 37% capacity retention after 300 cycles at 0.2C rate. Pouch cell assembled with 50 pm thin lithium and LFP cathode shows 69% capacity retention after 85 cycles.
[0088] Comparative Example 1
[0089] Take 1 mL of DOL and 1 mL of DME, mix the two solvents evenly, add 0.574 g of LiTFSI and 0.05 g of LiNO3 to the mixed solvent, stir for 5 min, continue to add 0.4 mL of PEGDA monomer and 0.0268 g of AIBN initiator, and stir evenly. After placing in an oven at 70°C for 4h, the prepared.
[0090] Figure 4 Electrochemical performance data of the GPE electrolyte obtained in Comparative Example 1: Figure 4 a in which is the conductivity data graph of the GPE electrolyte; Figure 4 b in which is the chronoamperometry test data graph of the GPE electrolyte.
[0091] fromFigure 4 It can be seen that the conductivity of the GPE electrolyte obtained in Comparative Example 1 is 9×10 -4 S cm -1 The lithium ion transference number of the GPE electrolyte obtained in Comparative Example 1 is 0.49.
[0092] In full cell tests, a high loading of 10 mg cm was used. -2 The Li||LFP full cell assembled with LFP cathode showed 123 mAh g after 85 cycles at 0.2C rate. -1 The capacity of a Li||NCM622 full cell assembled using a high-voltage NCM622 cathode with a cutoff voltage of 4.3V showed a capacity retention of 0% after 300 cycles at a 0.2C rate. A pouch cell assembled using a 50μm thin lithium and LFP cathode showed a capacity retention of 58% after 85 cycles.
[0093] Comparative Example 2
[0094] 1 mL of DOL and 1 mL of DME were measured and mixed evenly. 0.574 g of LiTFSI, 0.374 g of LiFSI and 0.05 g of LiNO3 were added to the mixed solvent and stirred for 5 minutes. 0.4 mL of PEGDA monomer and 0.0268 g of AIBN initiator were added and stirred evenly. The mixture was then placed in an oven and thermally polymerized at 70 ° C for 4 hours.
[0095] Figure 5 The electrochemical performance data of the GPE electrolyte obtained in Comparative Example 2 are as follows: Figure 5 Figure a is the conductivity data of GPE electrolyte; Figure 5 Figure b is the chronoamperometry test data of GPE electrolyte.
[0096] Depend on Figure 5 It can be seen that the conductivity of the GPE electrolyte obtained in Comparative Example 2 is 1.82×10 -3 S cm -1 The lithium ion transference number of the GPE electrolyte obtained in Comparative Example 2 is 0.78.
[0097] In full cell tests, a high loading of 10 mg cm was used. -2 The Li||LFP full cell assembled with an LFP cathode showed 139 mAh g after 300 cycles at 0.2C rate. -1 The capacity of a Li||NCM622 full cell assembled using a high-voltage NCM622 cathode with a cutoff voltage of 43V showed a capacity retention rate of 67% after 300 cycles at a 0.2C rate. The capacity retention rate of a pouch cell assembled using a 50μm thin lithium and LFP cathode was 81% after 85 cycles.
[0098] Comparative Example 3
[0099] Take 1 mL of DOL and 1 mL of DME, mix the two solvents evenly, add 0.574 g of LiTFSI, 0.2 mL of PFPN and 0.05 g of LiNO3 to the mixed solvent, stir for 5 min, continue to add 0.4 mL of PEGDA monomer and 0.0268 g of AIBN initiator, stir evenly and then place in an oven for heat polymerization at 70°C for 4 h to prepare.
[0100] Figure 6 The electrochemical performance data of the GPE electrolyte obtained in Comparative Example 3 are as follows: Figure 6 Figure a is a graph of the conductivity data of the GPE electrolyte; Figure 6 Figure b is a graph of the chronoamperometry test data of the GPE electrolyte.
[0101] From Figure 6 It can be seen that the conductivity of the GPE electrolyte obtained in Comparative Example 3 is 1.1 x 10 -3 S cm -1 The number of lithium ion transfers of the GPE electrolyte obtained in Comparative Example 3 is 0.62.
[0102] In the full cell test, a high loading of 10 mg cm -2 The Li||LFP full cell assembled with the LFP cathode showed a capacity of 133 mAh g -1 at 0.2C rate after 300 cycles. The Li||NCM622 full cell assembled with the high voltage NCM622 cathode with a cutoff voltage of 4.3 V showed a capacity retention of 62% at 0.2C rate after 300 cycles. The pouch cell assembled with 50 pm thin lithium and LFP cathode showed a capacity retention of 77% after 85 cycles.
[0103] Comparative Example 4
[0104] Take 1 mL of DOL and 2 mL of TTE, mix the two solvents evenly, add 0.574 g of LiTFSI, 0.2 mL of PFPN and 0.05 g of LiNO3 to the mixed solvent, stir for 5 min, continue to add 0.4 mL of PEGDA monomer and 0.0268 g of AIBN initiator, stir evenly and then place in an oven for heat polymerization at 70°C for 4 h to prepare.
[0105] The conductivity of the GPE electrolyte obtained in Comparative Example 4 is 0.79 mS cm -1 , and the number of lithium ion transfers is 0.32.
[0106] In the full cell test, a high loading of 10 mg cm -2 The Li||LFP full cell assembled with the LFP cathode showed a capacity of 133 mAh g-1 The capacity retention of Li||NCM622 full cells assembled using a high voltage NCM622 cathode with a cutoff voltage of 4.3 V was 12% after 300 cycles at 0.2C rate. The capacity retention of pouch cells assembled using 50 pm thin lithium and LFP cathode was 23% after 85 cycles.
[0107] The above merely describes the preferred embodiments of the present application, and it should be noted that those skilled in the art can make several improvements and refinements without departing from the principles of the present application, and these improvements and refinements should also be considered as the protection scope of the present application.
Claims
1. A gel polymer electrolyte, characterized in that: The preparation includes the following raw materials: Polar organic solvents, lithium salts, lithium salt additives, liquid flame retardants, liquid monomers and initiators; The polar organic solvent includes 1,3-dioxolane and ethylene glycol dimethyl ether; The ratio of the lithium salt to the polar organic solvent is 1 mmol: 0.5-2 mL; The mass of the lithium salt additive is 1.5-5% of the total mass of the lithium salt and the polar organic solvent; The volume of the liquid flame retardant is 10 to 20% of the volume of the polar organic solvent; The volume of the liquid monomer is 10-20% of the volume of the polar organic solvent; The mass of the initiator is 0.5-2% of the total mass of the lithium salt, the polar organic solvent and the liquid monomer.
2. The gel polymer electrolyte according to claim 1, characterized in that The volume ratio of the 1,3-dioxolane to ethylene glycol dimethyl ether is 1:0.5-2.
3. The gel polymer electrolyte according to claim 1, characterized in that The lithium salt includes one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl imide) and lithium bis(fluorosulfonyl imide).
4. The gel polymer electrolyte according to claim 1, characterized in that The lithium salt additive includes one or more of a derived unsymmetrical (fluorosulfonyl) (trifluoromethanesulfonyl) imide lithium, lithium hexafluorophosphate, lithium difluorobisoxalate phosphate, lithium difluorophosphate, lithium tetrafluorooxalate phosphate, lithium difluorooxalatoborate and lithium nitrate.
5. The gel polymer electrolyte according to claim 1, characterized in that The liquid flame retardant includes an organic phosphorus flame retardant, a nitrogen-containing flame retardant and a fluorine-containing flame retardant; The organophosphorus flame retardant includes one or more of trimethyl phosphate, triethyl phosphate, triphenyl phosphate, diethyl (2,2,2-trifluoroethyl) phosphate and triethyl hexafluorophosphate; The nitrogen-containing flame retardant includes melamine cyanurate and / or melamine; The fluorine-containing flame retardant includes one or more of bis(2,2,2-trifluoroethyl)phosphate, perfluoropolyether, ethoxy(pentafluoro)cyclotriphosphazene and 1-ethyl-3-methylimidazolium hexafluorophosphate.
6. The gel polymer electrolyte according to claim 1, characterized in that The liquid monomer includes one or more of a polyether monomer, an acrylate monomer and a fluorine-containing monomer; The polyether monomers include ethylene oxide and / or propylene oxide; The acrylic acid ester monomers include polymethyl methacrylate and / or polyethylene glycol diacrylate; The fluorine-containing monomer includes vinylidene fluoride and / or Nafion precursor.
7. The gel polymer electrolyte according to claim 1, characterized in that The initiator includes a peroxide thermal initiator and / or an azo thermal initiator; The peroxide thermal initiator includes dibenzoyl peroxide and / or dicumyl peroxide; The azo thermal initiator includes azobisisobutyronitrile and / or diethyl azodicarboxylate.
8. The method for preparing the gel polymer electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials for preparing the gel polymer electrolyte are mixed and then in-situ polymerized to obtain the gel polymer electrolyte.
9. The preparation method according to claim 8, characterized in that The temperature of the in-situ polymerization is 50-70° C., and the time is 4-12 hours.
10. Use of the gel polymer electrolyte according to any one of claims 1 to 7 or the gel polymer electrolyte prepared by the preparation method according to claim 8 or 9 in a lithium ion battery.
Citation Information
Cited By
Controllable polymerized gel electrolyte and preparation method thereof
CN121507082A
Controllable polymerization gel electrolyte and preparation method thereof
CN121507082B
Flame-retardant gel electrolyte, preparation method thereof and lithium ion battery containing electrolyte
CN121507084A